The effect of perennials as green manure on cereal productivity and disease incidence - Skuodiene, R.; Nekrosiene, R. (Spanish Journal of Agricultural Research, 2012)
<span style="font-size: 11pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">Field experiments were conducted at the Vezaiciai Branch of the Lithuanian Research Centre for Agriculture and Forestry during the period 2002-2007. They were designed to ascertain the effects of phytomass of different perennial pre-crops used for green manure on the productivity and on the occurrence of foliar fungal diseases of cereal agrocenoses. Plant residues and phytomass ploughed down as green manures positively affected cereal indices of crop productivity not only for the first but for the second year as well. It influenced the productivity of cereal segments. The largest amount of metabolizable energy was in the yield of cereal sequence under white clover (Trifolium repens L.) —83.23-84.76% GJ ha–1. The potential accumulated by perennials of the second year of development was more efficiently utilised by winter triticale (Triticosecale Wittm.) cv. ‘Tevo’, and that of perennials of the third year of development was more efficiently utilised by spring barley (Hordeum vulgare L.) cv. ‘Ula’. Perennials had a significant effect on the spread of foliar diseases in winter triticale (Triticosecale Wittm.) and spring barley (Hordeum vulgare L.) agrocenoses. The severity of the disease was 1.1-1.3 times higher in the winter triticale (Triticosecale Wittm.) treatments with white clover (Trifolium repens L.) pre-crops. Foliar disease incidence and severity was 1.1-1.2 times higher in the agrocenoses of spring barley (Hordeum vulgare L.) after legumes of the third year of development, especially after lucerne (Medicago sativa L.).